Work Stress and Procrastination on Self-management and Academic Performance of Lecturers: Case Study at a Private University in Serang City, Indonesia - Rochani Rochani; Syadeli Hanafi; Yuyu Yuhana (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The following variables will be examined in this research to determine their respective influences: (1) the direct impact of stress on academic performance; (2) the direct impact of stress on self-management; (3) the direct impact of procrastination on academic performance; (4) the direct impact of procrastination on self-management; and (5) the direct impact of self-management on academic performance. Explanatory research is the methodology utilized in the study to explain the variables examined and provide a causal relationship between variables through hypothesis testing. This research examines the direct and indirect effects of stress, work, and procrastination on Self-Management and Academic Performance. The sample in this research was lecturers from the University in Serang City, Indonesia. Remember the population of around 100-200 people. Then, for technique, data collection uses a saturated (complete) sample, where all populations make a sample. The tools used in this research, apart from computers (laptops), are (1) Microsoft Office (Word, Excel, PowerPoint, and Visio) and (2) Smart-PLS 3.2.9 Professional. Results: The research involved 110 respondents in a study. In part, most respondents are in a group aged 31-40 years, with as many as 48 lecturers (43.64 %). Sex between men and women was almost balanced, with men at 57 (51.82 %) and women at 53 (48.18 %). Qualification _ There were 103 postgraduate academics (93.64%) and seven postgraduate academics (6.36%). Statistical test results show that stress positively affects academic performance, indicated by a parameter coefficient of 0.053. Thus, the hypothesis (H1) cannot be accepted: Stress has a positive but insignificant effect on academic performance. Hypothesis 2 (H2): Procrastination positively affects Academic Performance, indicated by a parameter coefficient of 0.054. Thus, the hypothesis can be accepted: Procrastination has a positive but insignificant effect on Academic Performance. Hypothesis 3 (H3): Stress positively affects self-management; this is indicated by a parameter coefficient of 0.482. Thus, the hypothesis can be accepted: Stress positively and significantly affects Self-Management. Hypothesis 4 (H4): Procrastination positively affects self-management, indicated by a parameter coefficient of 0.324. Thus, the hypothesis can be accepted: Procrastination positively and significantly affects academic performance. Hypothesis 5 (H5): Self-management positively affects academic performance, indicated by a parameter coefficient of 0.809. Thus, the hypothesis can be accepted: Self-Management positively and significantly affects Academic Performance.